Second Order Horner Syndrome Concurrent with Brachial Plexus Injury Following Thyroid Radiofrequency Ablation: A Case Report - Wijaya, Thedi Darma; Saputri, Kevin Mulya; Purwanto, Denni Joko (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Introduction: Radiofrequency ablation (RFA) is a non-invasive, yet effective treatment of thyroid nodule. Complications following procedure is reported below 5%. Here, we report a case of Horner syndrome (HS) concurrent with brachial plexus injury (BPI) following RFA. Case Report: A 20-year old female underwent the left thyroid US-guided RFA. She complained of dropped left eyelid, left arm weakness, numbness and tingling sensation on left index finger following surgery. On neurological examination; there were left-sided reduced pupil size on dim light (4 mm/2mm), eye ptosis (6 mm palpebral fissure height), face hypohydrosis, arm weakness (3444+), reduced physiological reflexes, and C5-6 hypesthesia. There was prominent edema extending from left thyroid to whole trunk of left brachial plexus as shown on cervical MRI. The patient was given a high dose methylprednisolone and mecobalamin injection for five days. There was notable improvement on the following month - increased left eye palpebral fissure to 8 mm, equal pupil on dim light, increased left arm strength (44+55) and physiological reflexes. Nonetheless, allodynia on the left shoulder and upper arm persisted. Discussion: Although RFA theoretically produces less power and damage per unit time, it can cause neurological complications. Heat dissipated to surrounding neural tissue including brachial plexus and sympathetic trunk. This patient developed second order HS and BPI due to edema following injury to surrounding middle cervical sympathetic ganglion and brachial plexus. Apt treatment can prevent persistent neurological deficits. Conclusion: HS and BPI are important neurological complications that should be acknowledged following thyroid RFA.